Government project failure in Ghana: a multidimensional approach. Issue 1 (4th January 2017) - Damoah, Isaac Sakyi; Akwei, Cynthia
Abstract : Purpose: The purpose of this paper is to assess the extent of failure within Ghanaian Government projects using multiple failure criteria. Design/methodology/approach: This study used a sequential data collection approach by employing an in-depth semi-structured interview and questionnaire, respectively. Based on insight from the literature review, interviews were held with participants to solicit their perceptions about the failure of Ghanaian Government projects. A questionnaire was developed based on the results from the interviews in order to determine the relative importance of the various failure criteria used as the evaluation tool. Findings: Six main criteria were identified and used as the assessment framework for Ghanaian Government project failure. The findings indicated that Ghanaian Government projects fail on all the six failure criteria; however, the extent of failure differs from criterion to criterion. The worst failure criterion is meeting the projected timescale. This is followed by cost, requirement, stakeholder satisfaction, national development and contribution to the sector where projects are implemented, respectively. Practical implications: From this study, government project practitioners and policy makers will be able identify the failure areas (criteria) on which to focus during government project implementation. Originality/value: Though extant literature has been devoted to the success/failure criteria, attention has not been paid to comparison of the extent of failure within these criteria in government projects. Therefore, this study extends the literature in this regard as well as government project failure literature in general.